Strengthening the Moral Value of PPKn Learning as an Effort to Prevent Bullying at SMPN 2 Padangan Class 7C: Penguatan Nilai Moral Pembelajaran PPKn sebagai Upaya Pencegahan Bullying di SMPN 2 Padangan Kelas 7C - Reskhy Illhammi Eka Putri; Nuswantari Nuswantari; Yuni Harmawati (ITScience (Information Technology and Science), 2026)
The phenomenon of bullying at the junior high school level continues to increase every year and has the potential to damage the learning climate and psychosocial development of students. Pancasila and Citizenship Education Learning (PPKn) has a strategic position as a space to strengthen moral values, empathy, and tolerance that can prevent bullying behavior, especially for grade 7C students of SMPN 2 Padangan who are in a period of social and emotional transition. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews with PPKn teachers and 24 students of class 7C, direct observation during the learning process, and a study of school policy and curriculum documentation related to bullying prevention. PPKn teachers apply moral values through contextual and dialogical approaches, such as discussions of moral dilemmas, exemplary attitudes, and the use of interactive learning media. This implementation is influenced by internal factors, namely self-concept, knowledge about bullying, and student self-control, as well as external factors, namely school culture, teacher examples, counseling guidance service support, community and parent involvement, and learning media. Students' perceptions of strengthened moral values show a positive response in the form of increased empathy, tolerance, and courage to reprimand peers' negative behavior. PPKn learning that emphasizes the internalization of moral values dialogically and contextually, supported by interrelated internal and external factors, has been proven to contribute significantly to preventing bullying behavior and shaping the citizenship character of grade 7C students of SMPN 2 Padangan.